Drosophila model of Meier‐Gorlin syndrome based on the mutation in a conserved C‐Terminal domain of Orc6. (2nd July 2015) - Balasov, Maxim; Akhmetova, Katarina; Chesnokov, Igor
<x xml:space="preserve">Abstract</x> Meier‐Gorlin syndrome (MGS) is an autosomal recessive disorder characterized by microtia, primordial dwarfism, small ears, and skeletal abnormalities. Patients with MGS often carry mutations in the genes encoding the components of the pre‐replicative complex such as Origin Recognition Complex (ORC) subunits Orc1, Orc4, Orc6, and helicase loaders Cdt1 and Cdc6. Orc6 is an important component of ORC and has functions in both DNA replication and cytokinesis. Mutation in conserved C‐terminal motif of Orc6 associated with MGS impedes the interaction of Orc6 with core ORC. In order to study the effects of MGS mutation in an animal model system we introduced MGS mutation in Orc6 and established Drosophila model of MGS. Mutant flies die at third instar larval stage with abnormal chromosomes and DNA replication defects. The lethality can be rescued by elevated expression of mutant Orc6 protein. Rescued MGS flies are unable to fly and display multiple planar cell polarity defects. © 2015 Wiley Periodicals, Inc.